A high-performance nonlinear metasurface for spatial-wave absorption - Luo, Zhangjie (2022)
Nonlinear absorption is a significant topic in classic nonlinear sciences. Today, a growing interest in this area is drawn by increasingly severe interferences associated with strong microwaves. Although conventional absorbers may help mitigate the harmful effects, they unavoidably cause a huge loss to small useful signals. Here, a novel nonlinear absorbing metasurface is proposed targeting spatial waves. Based on an active nonlinear mechanism, the input impedance of the metasurface is highly dependent on the wave intensity. When the waves get stronger, the impedance-match between the meta-surface and free space is improved, so they are preferably allowed to enter the structure and be dissipated inside. A prototype is fabricated and measured in a microwave anechoic chamber, and its intriguing characteristics such as wide incident angle scope, dual polarizations, and wide instantaneous bandwidth are demonstrated, which are in good agreement with theoretical and simulated anticipations. With an ultralow profile and a simple direct-current-supplying strategy, the proposal can find potential applications in various scenarios to reinforce the protection of the weak against the strong.